4w-4x-y+3w+18x-8y=

Simple and best practice solution for 4w-4x-y+3w+18x-8y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4w-4x-y+3w+18x-8y= equation:


Simplifying
4w + -4x + -1y + 3w + 18x + -8y = 0

Reorder the terms:
4w + 3w + -4x + 18x + -1y + -8y = 0

Combine like terms: 4w + 3w = 7w
7w + -4x + 18x + -1y + -8y = 0

Combine like terms: -4x + 18x = 14x
7w + 14x + -1y + -8y = 0

Combine like terms: -1y + -8y = -9y
7w + 14x + -9y = 0

Solving
7w + 14x + -9y = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-14x' to each side of the equation.
7w + 14x + -14x + -9y = 0 + -14x

Combine like terms: 14x + -14x = 0
7w + 0 + -9y = 0 + -14x
7w + -9y = 0 + -14x
Remove the zero:
7w + -9y = -14x

Add '9y' to each side of the equation.
7w + -9y + 9y = -14x + 9y

Combine like terms: -9y + 9y = 0
7w + 0 = -14x + 9y
7w = -14x + 9y

Divide each side by '7'.
w = -2x + 1.285714286y

Simplifying
w = -2x + 1.285714286y

See similar equations:

| 2x+8=3-2x | | 1=9-3 | | T-(x-8)=-2 | | 18P-226=48 | | (x-4)(x^2+3)-(x-4)(6x-2)=0 | | -10+4x=2x-16 | | 70=10u | | 5x/95 | | 13+4(x+3)=105 | | 5+3A=7A-56 | | 3a+5=4 | | 2x^2+5x+(3-3k)=0 | | n^2-22n+40=0 | | 10x-2y+10w+7y-3w+4c= | | 17=15+w-5 | | 3(2X-4)=X+3 | | 6m-10=28 | | 9x-1=63-7x | | 3k+6=14 | | (x-3)(y+5)=xy-19 | | 4n^2=-6n-1 | | y=0.2x^2+0.15x+0.8 | | 3c-1=c+a | | 2H-32=5H-7 | | 3sin^2x=cosx | | -2x-6=5x-10 | | 7y=-3x+4 | | 4//4/5 | | 57=9p+3 | | 4w+4y+8x+6x-13y+4w= | | 7-3A=19 | | -1/5r=(4)4/5 |

Equations solver categories